Impact of Shopee Promotions on Spontaneous Buying in Pematangsiantar - Julyanthry, Julyanthry; Suryati, Lili; Mamadiyarov, Zokir; Silalahi, Marto; Judijanto, Loso; Simanjuntak, Markus Doddy; Baxtishodovich, Sobirov Bobur (Aptisi Transactions On Technopreneurship (ATT), 2025)
This study aims to determine the impulse buying behavior influenced by the Shopee marketplace sales promotion in the Sibatu-batu Block 9 community, Sitalasari, Pematangsiantar city. This study uses a library research design and field research. The sample of this study was 38 people. The types of data used in this study are qualitative and quantitative data, while the data sources consist of primary data and secondary data. Data collection was carried out through interviews, questionnaires, and documentation. The analysis techniques used include normality tests, qualitative descriptive analysis, and quantitative descriptive analysis. The results of this study show that sales promotion is good and impulse buying is high, and there is a strong and positive relationship between the two variables. The findings also indicate that variations in impulse buying can be explained by sales promotion, and the hypothesis test confirms that H0 is rejected, meaning that sales promotion significantly affects impulse buying on the Shopee marketplace. Based on these findings, the study suggests that Shopee should consider re-adjusting the minimum purchase requirements to obtain shipping discounts, especially for areas outside Sumatra, in order to improve the effectiveness of sales promotion. Furthermore, to increase impulse buying, Shopee is advised to add time and quantity limits combined with tiered discounts.